Sitagliptin Suppresses Apoptotic Cell Death and Histological Changes in the Ovaries of Rats with Polycystic Ovary Syndrome - Safaeian, Azadeh; Zare Mehrjerdi, Fatemeh; Yadegari, Maryam; Rezvani, Mohammad Ebrahim (Archives of Medical Laboratory Sciences, 2021)
Background and Aim: Polycystic ovary syndrome (PCOS) is the most typical endocrine disorder affecting reproductive-aged women. The patients with PCOS show decreased follicular granule cells’ maturation in their ovaries, probably associated with cell apoptosis. This study was designed to investigate Sitagliptin’s protective effect against the apoptotic mechanism in PCOS via evaluating apoptosis rate and the mRNA expressions of apoptotic and anti-apoptotic molecules in PCOS rats. Methods: PCOS was induced by injection of estradiol valerate (4 mg/kg, I.M.). Twenty-two female rats divided into four groups: Control (n=5), PCOS+Vehicle (n=5), PCOS+ Sitagliptin 25 mg/kg (n=6) and PCOS+ Sitagliptin 50 mg/kg (n=6). Hematoxylin and eosin staining were used to determine qualitative changes in the ovary follicles. The apoptotic index was examined by TUNEL assay, and the quantitative polymerase chain reaction was performed to detect expression levels of Bax and Bcl-2. Results: Bax mRNA expression was up-regulated (1.38-folds), and Bcl-2 mRNA expression was down-regulated (0.45-folds) in PCOS rats’ ovarian tissues. Sitagliptin did not change Bax expression but increased the Bcl-2 mRNA expression (1.95-folds). The apoptosis index was increased in the PCOS group compared with the control group. The number of cystic follicles and pre-antral follicles increased the number of corpus luteum was decreased in PCOS rats compared to control rats. Sitagliptin decreased apoptosis rate and prevented the increase of cystic and pre-antral follicle numbers compared to the PCOS group. Conclusion: In conclusion, Sitagliptin might have a major role in preventing PCOS development due to its anti-apoptotic properties on PCOS rats’ ovaries. *Corresponding Author: Mohammad Ebrahim Rezvani, Email: me.rezvani@ssu.ac.ir; ORCID: https://orcid.org/0000-0001-6146-806X Please cite this article as: Safaeian A, Zare Mehrjerdi F, Yadegari M, Ebrahim Rezvani M. Sitagliptin Suppresses Apoptotic Cell Death and Histological Changes in the Ovaries of Rats with Polycystic Ovary Syndrome. Arch Med Lab Sci. 2021;7:1-9 (e22). https://doi.org/10.22037/amls.v7.34952